VOTING BEHAVIOR RESPONSES TO WOM (WORD-OF-MOUTH) AND EWOM (ELECTRONIC WORD-OF-MOUTH) INFORMATION - Zen-U Hotta,; Masato Eguchi, (Politology, 2023)
Decision making is often influenced by external information, especially opinions of others.Though past studies revealed that both WOM (word-of-mouth) and EWOM (electronic word-of-mouth) information influences on decision making, little has been investigated and found out in the field of voting behavior, with the possible exception of the fact that several categories of WOM factors influence on voting. As voters face multiple WOM and EWOM information concerning various characteristics of political candidates in real life, it is important to know how they prioritize some information over others. On such backdrop, this study attempts to see how much weight voters would put on 640 types of information – positive and negative information on 16 types of candidate characteristics coming from 20 different WOM and EWOM sources. Two facts have come out. One is that voters prioritize positive information over negative information of the same candidate characteristic, with the exceptions of relationship with family members, campaign activity, and news/scandal of candidate.Another is that voters prioritize WOM information over EWOM information on the same candidate characteristic, regardless of whether the information is positive or negative, for all characteristics.